2022
DOI: 10.1073/pnas.2120913119
|View full text |Cite
|
Sign up to set email alerts
|

An extended conformation of SARS-CoV-2 main protease reveals allosteric targets

Abstract: Significance The coronavirus main protease (M pro ) is required for viral replication. Here, we obtained the extended conformation of the native monomer of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) M pro by trapping it with nanobodies and found that the catalytic domain and the helix domain dissociate, revealing allosteric targets. Another monomeric state is termed compact conformation and is similar to one protomer of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 35 publications
2
27
0
Order By: Relevance
“…However, in our work, we also report on a residue community analysis of the enzyme, which notably suggested that CCG‐50014 disrupted inter‐community correlations stemming for the catalytic residues C145 and H41. These observations highlight the role of allostery in this enzyme, which could prove useful in designing potential therapeutics targeting the enzyme via an allosteric mechanism 75–77 …”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…However, in our work, we also report on a residue community analysis of the enzyme, which notably suggested that CCG‐50014 disrupted inter‐community correlations stemming for the catalytic residues C145 and H41. These observations highlight the role of allostery in this enzyme, which could prove useful in designing potential therapeutics targeting the enzyme via an allosteric mechanism 75–77 …”
Section: Resultsmentioning
confidence: 90%
“…These observations highlight the role of allostery in this enzyme, which could prove useful in designing potential therapeutics targeting the enzyme via an allosteric mechanism. 75 , 76 , 77 …”
Section: Resultsmentioning
confidence: 99%
“…In this sense, El-Baba and colleagues ( 61 ) identified that fragment JGY—discovered through crystallographic fragment screening and binding in the dimer interface ( 30 )—destabilized the Mpro dimer and showed ∼35% inhibition of the rate of processing at 100 μM. Along the same lines, Sun and colleagues ( 62 ) discovered a nanobody, NB2B4, which binds the C-terminal domain of monomeric Mpro (PDB 7VFB) and inhibits activity with an IC 50 ∼150 nM. Thus, destabilization of the Mpro catalytic dimer may contribute to the mechanism of inhibition.…”
Section: Discussionmentioning
confidence: 94%
“…The model retrieved from PDB is the monomer form of protease. However, the global stoichiometry of the protease is homodimer [6] , [37] . Therefore, for the dimer simulations, protein-protein docking was carried out using HDOCK server [38] .…”
Section: Methodsmentioning
confidence: 99%